2021
DOI: 10.3390/cells10081974
|View full text |Cite
|
Sign up to set email alerts
|

UBE2L3, a Partner of MuRF1/TRIM63, Is Involved in the Degradation of Myofibrillar Actin and Myosin

Abstract: The ubiquitin proteasome system (UPS) is the main player of skeletal muscle wasting, a common characteristic of many diseases (cancer, etc.) that negatively impacts treatment and life prognosis. Within the UPS, the E3 ligase MuRF1/TRIM63 targets for degradation several myofibrillar proteins, including the main contractile proteins alpha-actin and myosin heavy chain (MHC). We previously identified five E2 ubiquitin-conjugating enzymes interacting with MuRF1, including UBE2L3/UbcH7, that exhibited a high affinit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
10
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 13 publications
(10 citation statements)
references
References 63 publications
0
10
0
Order By: Relevance
“…Atrogin-1 and MuRF-1 were two key musclespecific E3 ubiquitin ligases regarded as the markers of muscle atrophy, and also proved to be related to the mechanisms of BJD improving muscle atrophy in cancer cachexia (Bodine and Baehr, 2014;Zhang et al, 2017;Zhang et al, 2018;Wang et al, 2020). Studies have shown that atrogin-1 and MuRF-1 targeted several myofibrillar proteins for degradation, including a-actin within the ubiquitin-proteasome system (Peris-Moreno et al, 2021). Considering that we have previously proved that BJD treatment inhibited the protein expressions of atrogin-1 and MuRF-1 in Apc Min/+ mice (Supplementary Figure S2), we detected the protein expression of a-actin and MyoD in this study (Figures 2E,F).…”
Section: Discussionmentioning
confidence: 99%
“…Atrogin-1 and MuRF-1 were two key musclespecific E3 ubiquitin ligases regarded as the markers of muscle atrophy, and also proved to be related to the mechanisms of BJD improving muscle atrophy in cancer cachexia (Bodine and Baehr, 2014;Zhang et al, 2017;Zhang et al, 2018;Wang et al, 2020). Studies have shown that atrogin-1 and MuRF-1 targeted several myofibrillar proteins for degradation, including a-actin within the ubiquitin-proteasome system (Peris-Moreno et al, 2021). Considering that we have previously proved that BJD treatment inhibited the protein expressions of atrogin-1 and MuRF-1 in Apc Min/+ mice (Supplementary Figure S2), we detected the protein expression of a-actin and MyoD in this study (Figures 2E,F).…”
Section: Discussionmentioning
confidence: 99%
“…PI3K/AKT/mTOR signalling pathway silencing and aging-induced inflammation can activate the UPS, which decreases contractile proteins and increases the average distance between MyHC and F-actin. 57 Muscle fibre atrophy and reductions in muscle fibre-specific force and unloaded shortening velocity are widely recognized as significant contributors to the development of sarcopenia. 8 Under energy stress, AMPK phosphorylates FoxO3 Ser413/588 and activates it.…”
Section: Ubiquitinationmentioning
confidence: 99%
“…MuRF1 can targets for degradation several myofibrillar proteins, and UBE2L3 exhibited a high affinity for MuRF1. 18,19 Intermittent exercise can reduce the expression of MuRF1 by inhibiting NF-κB to improve the degradation of skeletal muscle protein. Similarly, endurance training can also inhibit the activation of NF-κB, thereby reducing the expression of MAFbx and MuRF1, and reducing the occurrence of skeletal muscle atrophy.…”
Section: Nf-κb / Murf1 Pathway and Mechanisms Of Muscle Atrophymentioning
confidence: 99%